THE INFLUENCE OF SOCIAL WARANNTY ON THE CHANGE OF THE BEHAVIOR OF SUKU LAUT COMMUNITIES IN THE VILLAGE IN THE SUB-DISTRICT OF TELUK SEBONG DISTRICT OF BINTAN PROVINCE OF RIAU ISLANDS - Eltri Febrina Hutabarat; Ridar Hendri; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT               This research was conducted in May 2017 at Berakit Village, Teluk Sebong Sub-district, Bintan Regency, Kepulauan Riau Province. The purpose of this study was to identify social warannty forms, to describe social security mechanisms, and to know the effect of social warranty on behavioral changes of the Suku Laut community.This research method is qualitative method, informant determined with snowball sampling, and data were analyzed using descriptive analysis.              The results show that the existing forms of social warannty in the Suku Laut Community are the guarantee of education, health insurance, food clothing, housing security, and job and business warannty.The mechanism for obtaining social warranty in the Suku Laut Community is formal and informal.With the social warannty obtained by the Suku Laut Community, there will be behavioral changes such as residential change, economy, attitude / behavior, spiritual change/ belief and lifestyle changes both transportation and communication in the community. Keywords: social warranty, behavior change, Suku Laut, Bintan(1) Students in the Faculty of Fisheries and Marine University of Riau(2) Lecturer in Faculty of Fisheries and Marine University of Riau